Gorgeous - Rudnick, Paul 1957- (Scholastic Press, 2013)
When eighteen-year-old Becky Randle's mother dies, she is whisked away from a trailer park to New York City, where fashion designer Tom Kelly offers to transform her into a glamorous Rebecca, a girl fit for a prince...but soon she begins to fear that she will lose touch with her real self
Keywords: Identity (Psychology) -- Juvenile fiction; Beauty, Personal -- Juvenile fiction; Princes -- Juvenile fiction; Identity; Beauty, Personal; Princes; Jugendbuch